Gold nanoparticle based anisotropic nanocomposites : fabrication, assembly and application - Tao, Chen (2010)
This thesis deals mainly with colloidal anisotropic nanostructures composed of Au nanoparticle and polymer. In the nanocomposites, one side of the Au nanoparticle was encapsulated by polymer; the other side was functionalized with hybrophilic molecule, generating Janus-like morphology. Ligand segregation on the Au surface dictated the polymer attachment. By controlling the ligand competition under the assistance of polymer attachment, a standard route to localize analytes on specific sites of anisotropic nanostuctures, such as the ends or sides of gold nanorods, was developed. This type of ligand assignment enabled us to record the surface-enhanced Raman scattering from specific areas of Au nanorods. In addition, nanoparticle dimers and linear chains of the nanocomposites were obtained by salt induced aggregation. The controllable organization of anisotropic nanocomposites allows the creation of uniform hot spots to investigate the surface-enhanced Raman scattering fingerprint variations. As a step further to anisotropic Au nanoparticle and polymer, the ligand competition methodology was extended to the investigation of Janus Au-SiO2 and ternary Ag-Au-SiO2 nanostuctures.